Efficacy of Toothpaste Containing Nano Calcium in Dentin Remineralization - Anton Rahardjo; Desita Dyah Tri Nugraheni; Ghina Humaira; Melissa Adiatman; Diah Ayu Maharani (Makara Journal of Health Research, 2015)
Brushing teeth with toothpaste is the most effective method of removing plaque, preventing dental caries and repairing early caries. This research aims to conduct an efficacy test of toothpaste containing nano calcium as an active ingredient in repairing early caries over two weeks. A double-blind randomized parallel group clinical trial was conducted. Eighteen people were randomly assigned to use the test toothpaste, and eighteen others were assigned to use the control toothpaste. Assessments of early caries with DIAGNOdent Pen were performed before and after two weeks of toothpaste use. The results showed that the test toothpaste was more effective in repairing early caries over two weeks than the control toothpaste. Toothpaste containing nano-calcium has the potential to accelerate the healing of early dental caries.